Impacts of Taxation on Economic Growth in Africa in 2008-2018 - Panel Data Analysis - Kessy, Mercy; Sukartini, Ni Made (Journal of Developing Economies, 2023)
The debate over the effectiveness of taxes as a tool for promoting economic growth still needs to be solved, with several studies indicating mixed effects of taxes on economic growth. The purpose of this research is to assess the impact of taxation on economic growth in Africa. The study spans eleven years, from 2008 to 2018, and includes multiple variables for 21 African countries. GDP is a dependent variable used as a proxy for economic growth. Numerous GDP-determining predictors were utilized as independent variables; these variables were categorized into three groups: The supply side consists of human capital (population and literacy rate) and economic activities (trade and services). Demand side variables include consumption, government expenditures, net exports, and gross capital formation. Lastly, taxation variables consist of tax revenue, corporate tax rate, number of tax payments, personal income tax, and taxes on income, profits, and capital gains. The study conducted preliminary tests, including descriptive statistics, correlation matrix, and pooled least square estimations for panel data. Based on the results, all macroeconomic determinants have statistically significant effects on GDP except trade. Tax revenue and corporate tax rate positively affect GDP, while personal income tax rate and tax on income, profit, and capital gain negatively affect GDP. In general, taxation has a favorable effect on the economy of African countries because emerging countries use taxation as an internal key to generate revenue and improve economic growth.